Sistem Pendukung Keputusan Diagnosa Penyakit Tanaman Jeruk Menggunakan Metode Naive Bayes Classifier - Maskiswo Addi Puspito; Nurul Hidayat; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Because of CVPD virus attack in 2012, about 500 farmers in the south and west of Jember regency, East Java were forced to enlarge thousands of their citrus trees. While in other areas the citrus farmers were forced to cut down their citrus crops due to stricken fungus stems and citrus fruit can not be harvested. It takes a method that can be used to classify the types of symptoms of citrus plant disease. Naive bayes classifier is one of the suitable methods to be applied in the classification of the types of symptoms of citrus plant diseases. The reason for using the Naive Bayes Classifier method is because the Naive Bayes Classifier method is a simplification of the Bayes theorem. The variables needed in this study are the symptoms of the disease on the leaves, berries, stems and roots of citrus plants. This research resulted in a decision support system with 90% system accuracy.